Scott Polar Research Institute Arctic Airborne Radio-Echo Sounding Datasets: Canadian Arctic 2000 - Dowdeswell, Julian A; Benham, Toby; Gorman, Micheal R; Burgess, D; Sharp, Martin J (2021)
This data set contains radar sounder profiles from the SPRI 100 MHz ice-penetrating radar instrument over Devon and Ellesmere islands in the Canadian Arctic (CA). Along with the radar profile data, the archive includes derived and ancillary data, plus software code produced for acquisition and working up of data. The data were collected under funding from a UK Natural Environment Research Council (NERC) grant (GR3/12469) to Prof. J. A. Dowdeswell. Please consult the 'MetadataCA2000.pdf' file for a detailed description of the dataset and its contents. Funding: The collection of these data was funded by NERC grant GR3/12469 to J.A. Dowdeswell, as well as by grants from the Meteorological Service of Canada (CRYSYS program) to M.J. Sharp. Further funding (to J.A. Dowdeswell) for development of the dataset was provided by the NERC Centre for Polar Observation and Modelling, UK, and the EU SPICE Project.